Advanced AutoCAD 2015 : exercise workbook - Shrock, Cheryl R. (Industrial Press, Inc., 2014)
This book has been updated for AutoCAD 2015 and 2015 LT, offering several new and improved features. All exercises print easily on a standard 8 1/2" x 11" printer (for use with the PC version of AutoCAD 2015 only). Topics covered include: Xref, Attributes, and 3D solids; ability to capture, embed and plot maps with Geographic Location; dark color interface which includes the Ribbon, Status Bar and Palettes; greater control of the Enhanced Status Bar on the tools you want displayed; reorganized View Ribbon making it easier to control the visibility of the UCS Icon, Navigation Bar, ViewCube and Layout Tabs; improved graphics with Line Smoothing. --